The Guidance for Potential Development of Tour Guide in Songkhla Province and Linkage Areas (Phatthalung, Nakhon Si Thammarat, Pattani, Yala, Narathiwas and Satun) - jankingthong, wiwat; Jankingthong, Korkaew (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This research aims to assess, and make the guidelines for development of competency for a tour guide in Songkhla province and linkage areas . The samples size of the tour guide were 400 stratified random sampling. The 50 key informants for focus group were managers, private and government officers in tourism, tourists, communities, tour operators (owners /managers and personnel) and tour guides in the area of Songkhla, Phatthalung, Nakhon Si Thammarat, Pattani, Yala, Narathiwas and Satun. The research found that the competencies of the competencies of tour guides are at high level when considering each dimension by mean order as follows (1) ethics, (2) skills, and (3) knowledge. The guidance for potential development of tour guide in Songkhla Province and Linkage Areas have 3 main competency developments : 1) self-development strategies, 2) collaboration strategies, and 3) differentiate strategies.